An evaluation of WRF's ability to reproduce the surface wind over complex terrain based on typical circulation patterns. Issue 14 (25th July 2013) - Jiménez, P. A.; Dudhia, J.; González‐Rouco, J. F.; Montávez, J. P.; García‐Bustamante, E.; Navarro, J.; Vilà‐Guerau de Arellano, J.; Muñoz‐Roldán, A.
Abstract : [1] The performance of the Weather Research and Forecasting (WRF) model to reproduce the surface wind circulations over complex terrain is examined. The atmospheric evolution is simulated using two versions of the WRF model during an over 13 year period (1992 to 2005) over a complex terrain region located in the northeast of the Iberian Peninsula. A high horizontal resolution of 2km is used to provide an accurate representation of the terrain features. The multiyear evaluation focuses on the analysis of the accuracy displayed by the WRF simulations to reproduce the wind field of the six typical wind patterns (WPs) identified over the area in a previous observational work. Each pattern contains a high number of days which allows one to reach solid conclusions regarding the model performance. The accuracy of the simulations to reproduce the wind field under representative synoptic situations, or pressure patterns (PPs), of the Iberian Peninsula is also inspected in order to diagnose errors as a function of the large‐scale situation. The evaluation is accomplished using daily averages in order to inspect the ability of WRF to reproduce the surface flow as a result of the interaction between the synoptic scale and the regional topography. Results indicate that model errors can originate from problems in the initial and lateral boundary conditions, misrepresentations at the synoptic scale, or the realism of the topographic features. Key Points: Importance of a long period of analysis to identify misrepresentations The topographic representation is responsible for wind biases Errors at the synoptic scale hamper the benefits of high horizontal resolution